EFFECT OF OCF, ICF, FCF AND NET PROFIT ON STOCK RETURNS - Ferdinand Napitupulu; Prida Melva Silalahi; Alexander Folakhomi Dakhi; Isti Panjaitan; Wulan H. Simanjuntak (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This research was investigated in order to identify the effect of variable X on variable Y in the basic and chemical industrial sectors in manufacturing companies listed on the IDX for the period 2018 – 2020. Sourced on the independent variables are Operating Cash Flow, Investment Cash Flow, Funding Cash Flow and Net Profit, While the dependent variable is Stock Return where there are e6 basic industrial companies and chemical manufacturing companies listed on the IDX. The sample is 13 companies using 3 research periods so that 39 companies used are in accordance with the criteria. The procedure in this research is multiple linear regression analysis. Funding Cash Flow on Stock Return has a significant and significant effect on Stock Return and Net Income has a significant and insignificant effect on Stock Return. But also in the F test where operating cash flow, investment cash flow, funding cash flow and net income have a simultaneous effect on stock returns